Vpeljava cirkuških veščin v pouk športa oziroma športne vzgoje - Jereb, Jan (Šport (Ljubljana), 2022)
Interest in obtaining and learning about circus skills training has grown in our communities. Consequently, we can also find them in the curriculum of the non-mandatory subject “Physical education” in second triennium of primary school. In order to facilitate and implement the subject appropriately, physical education teachers or general teachers should also learn about it. Due to many of its beneficial influences on the development of children, we can integrate circus skill training into classes of obligatory subject physical education in primary and secondary schools, obligatory elective subject Sport in last triennium of primary school, sports oriented and outbound trips, afterschool or morning care, Minute for Health, Physical Activity Recess, and alternatively also plan extracurricular sport activities with students in which one or more of these skills are taught in depth. In this article you can find key terminology, presentation of circus skills, their influence on students, the benefits of integrating circus skill training in the school system and why, where and how physical education or general teachers can learn about it all.
Keywords: cirkus; pedagogika; poučevanje; šport; športna vzgoja; učni programi